Meretas Kesetaraan Peran Publik Perempuan - Musram Doso (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
Humans with male and female types should be seen by referring to their competence and skill capabilities, not their biological personality. Human biological structure is natural. If humans are still questioning this difference which then leads to the inequality of public social roles between one of these types, then it can be said that he is part of the patriarchal missionary. That's why there must be one among us who dares to voice and realize that the creation of the two types of humans has an implicit divine message, namely sharing roles.